Neuromodulation in multiple sclerosis. (November 2017) - Abboud, Hesham; Hill, Eddie; Siddiqui, Junaid; Serra, Alessandro; Walter, Benjamin
Neuromodulation, or the utilization of advanced technology for targeted electrical or chemical neuronal stimulation or inhibition, has been expanding in several neurological subspecialties. In the past decades, immune-modulating therapy has been the main focus of multiple sclerosis (MS) research with little attention to neuromodulation. However, with the recent advances in disease-modifying therapies, it is time to shift the focus of MS research to neuromodulation and restoration of function as with other neurological subspecialties. Preliminary research supports the value of intrathecal baclofen pump and functional electrical stimulation in improving spasticity and motor function in MS patients. Deep brain stimulation can improve MS-related tremor and trigeminal neuralgia. Spinal cord stimulation has been shown to be effective against MS-related pain and bladder dysfunction. Bladder overactivity also responds to sacral neuromodulation and posterior tibial nerve stimulation. Despite limited data in MS, transcranial magnetic stimulation and brain–computer interface are promising neuromodulatory techniques for symptom mitigation and neurorehabilitation of MS patients. In this review, we provide an overview of the available neuromodulatory techniques and the evidence for their use in MS.